Virally Mediated Overexpression of Glial-Derived Neurotrophic Factor Elicits Age- and Dose-Dependent Neuronal Toxicity and Hearing Loss - Akil, Omar; Blits, Bas; Lustig, Lawrence R; Leake, Patricia A (Human gene therapy, 2019)
Contemporary cochlear implants (CI) are generally very effective for remediation of severe to profound sensorineural hearing loss, but outcomes are still highly variable. Auditory nerve survival is likely one of the major factors underlying this variability. Neurotrophin therapy therefore has been proposed for CI recipients, with the goal of improving outcomes by promoting improved survival of cochlear spiral ganglion neurons (SGN) and/or residual hair cells. Previous studies have shown that glial-derived neurotrophic factor (GDNF), brain-derived neurotrophic factor, and neurotrophin-3 can rescue SGNs following insult. The current study was designed to determine whether adeno-associated virus vector serotype 5 (AAV-5) encoding either green fluorescent protein or GDNF can transduce cells in the mouse cochlea to express useful levels of neurotrophin and to approximate the optimum therapeutic dose(s) for transducing hair cells and SGN. The findings demonstrate that AAV-5 is a potentially useful gene therapy vector for the cochlea, resulting in extremely high levels of transgene expression in the cochlear inner hair cells and SGN. However, overexpression of human GDNF in newborn mice caused severe neurological symptoms and hearing loss, likely due to Purkinje cell loss and cochlear nucleus pathology. Thus, extremely high levels of transgene protein expression should be avoided, particularly for proteins that have neurological function in neonatal subjects.